A retained dead fetus for eight years in a didelphys uterus - Pant, P.R.; Sharma, J.; Giri, K.; Pradhan, N.; Thapa, T.P. (Journal of Institute of Medicine Nepal, 2007)
Case report: A case report of 32 years female with 3 childrens and a retained dead fetus for eight years in a didelphys uterus is discussed as a case report.